Archaeological history of Middle Holocene environmental change from fish proxies at the Monte Castelo archaeological shell mound, Southwestern Amazonia. (November 2020) - Prestes-Carneiro, Gabriela; Béarez, Philippe; Pugliese, Francisco; Shock, Myrtle Pearl; Zimpel, Carlos Augusto; Pouilly, Marc; Neves, Eduardo Góes
Monte Castelo, an archeological shell mound located on the southwestern periphery of the Amazon basin, is an artificial forest island occupied from the Middle to late-Holocene, and it contains one of the longest, continuous sequences of human occupation anywhere in the basin. Analysis of fish remains investigates fluctuations in the fish communities that are markers of changes in the paleoenvironment. The 8112 taxonomically identified remains document diagnostic taxa that are drought-tolerant (armoured catfishes, swamp-eels and tiger fishes) and from swampy environments, indicating probable occupation during low-waters periods. The results from Monte Castelo contrasts with the use of shell mounds as refuges from high-water season floods, a dominant hypothesis. A considerable shift in the nature of the fish spectrum occurred around 4000 BP with increased diversity; the number of taxa jumps from 18 to 48. The Middle Holocene occupations, from 6000 to 4000 BP, reflect long-term stability in drought-tolerant taxa collaborating with paleoecological evidence of dryer conditions. The post 4000 BP introduction of small-sized cichlids and characins suggests an initial exploitation of flooded forests. Archeological fish remains corroborate paleoenvironmental records of increased precipitation between the Middle and Late-Holocene. The probable replacement of some savanna areas by forest vegetation, and the accompanying alteration of aquatic landscapes, is documented through the presence/absence of certain taxa in Monte Castelo's occupations. This suggests new economic strategies and the exploitation of new ecological niches, as the fish remains correspond to approximately 80% of the vertebrate fauna throughout the archeological sequence.